Molecular docking of substituted schiff bases derived from s-benzyldithiocarbazate as potential anticancer agents - How, Fiona Ni Foong (Frontiers, 2018)
Background Breast cancer is one of the lethal diseases worldwide. According to the Malaysia National Cancer Registry Report (MNCR 2007-2011), 17.7% from 103,507 new cases of cancer detected throughout Malaysia was breast cancer. The current treatments available are chemotherapy and hormone therapy using tamoxifen. However, it causes some side effects, which includes extreme fatigue, loss appetite, and depression. Therefore, there is a need for more targeted and less side-effect anti-cancer drug. Substituted Schiff bases derived from S-benzyldithiocarbazate are well known for their profound anticancer activity. However, there is no relationship to correlate the structural variation with their anticancer activity. This study served as the very first premier work to uncover the structure-activity relationship of the substituted Schiff bases derived from S-benzyldithiocarbazate.